Integrating task-based instruction as an alternative approach in teaching reading comprehension at an upper secondary school in Hanoi: An action research - Trần, Thị Thủy (2020)
Developing reading comprehension ability is an important aspect in acquisition of a language. The present study focused on improving reading comprehension ability through Task-based Instruction (TBI). TBI is a methodology that develops from a focus on classroom tasks. The participants of the study were 100 students at from four classes of 11thgrade at FPT high school through a quasi-experimental design. The participants were divided into two groups, one control group (CG) andone experimental group (EG). An action research with a cycle of treatment was employed in this research. The participants received a pre-test, the instruction, and a post-test. The participants in EG were taught through TBI, whereas the others in CG were exposed to a traditional method. The comparison between CG and EGswere made through paired sample t-tests. The results revealed that the students in EGs outperformed CGs. The results are also supported by the gathered data from the questionnaires, interviews, and class observations. This study may have pedagogical implications for practitioners in the field and for syllabus designers to include appropriate tasks in English textbooks and English teachers/instructions to deliver the appropriate teaching methods to their students.